2016
DOI: 10.1186/s12891-016-1272-8
|View full text |Cite
|
Sign up to set email alerts
|

Does cognitive/physical screening in an outpatient setting predict institutionalization after hip fracture?

Abstract: BackgroundInstitutionalization after hip fracture is a socio-economical burden. We examined the predictive value of Instrumental Activities of Daily Living (IADL) and Mini Mental State Examination (MMSE) for institutionalization after hip fracture to identify patients at risk for institutionalization.MethodsFragility hip fracture patients ≥65 years of age (n = 584) were comprehensively examined at a geriatric outpatient clinic 4 to 6 months after surgery and followed 1 year postoperatively. A telephone intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…We found ten social factors under study in the included articles, which we grouped into three main categories/themes: Social support: (a) intervention to increase social contact (Magaziner, Simonsick, Kashner, Hebel, & Kenzora, ), (b) number of social outings (Cobey et al, ), (c) reported size of social network (Cresci, ; Marottoli, Berkman, Leo‐Summers, & Cooney, ; Mortimore et al, ; Oh & Feldt, ), (d) and social isolation (Landeiro, Gray, & Leal, ). Socioeconomic factors: (a) income (Kristensen, Thillemann, Pedersen, Soballe, & Johnsen, ; Orive et al, ; Shin et al, ; Thorne et al, ), (b) employment (Allegrante et al, ), (c) education and training (Allegrante et al, ; Kristensen et al, ; Shin et al, ; Thorne et al, ), (d) barriers to housing (as an indicator of social deprivation) (Thorne et al, ), (e) and neighbourhood crime rate (as an indicator of social deprivation) (Thorne et al, ). Living arrangement/institutionalisation (Hongisto et al, ; Morghen et al, ; Orive et al, ; Sylliaas et al, ; Thorne et al, ). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We found ten social factors under study in the included articles, which we grouped into three main categories/themes: Social support: (a) intervention to increase social contact (Magaziner, Simonsick, Kashner, Hebel, & Kenzora, ), (b) number of social outings (Cobey et al, ), (c) reported size of social network (Cresci, ; Marottoli, Berkman, Leo‐Summers, & Cooney, ; Mortimore et al, ; Oh & Feldt, ), (d) and social isolation (Landeiro, Gray, & Leal, ). Socioeconomic factors: (a) income (Kristensen, Thillemann, Pedersen, Soballe, & Johnsen, ; Orive et al, ; Shin et al, ; Thorne et al, ), (b) employment (Allegrante et al, ), (c) education and training (Allegrante et al, ; Kristensen et al, ; Shin et al, ; Thorne et al, ), (d) barriers to housing (as an indicator of social deprivation) (Thorne et al, ), (e) and neighbourhood crime rate (as an indicator of social deprivation) (Thorne et al, ). Living arrangement/institutionalisation (Hongisto et al, ; Morghen et al, ; Orive et al, ; Sylliaas et al, ; Thorne et al, ). …”
Section: Resultsmentioning
confidence: 99%
“…Reported outcomes associated with social factors across studies were divided into three categories: Physical functional recovery: There were eleven articles investigated the relationship between social factors and physical functional recovery after hip fracture (Allegrante et al, ; Cobey et al, ; Cree, Carriere, Soskolne, & Suarez‐Almazor, ; Cresci, ; Egan et al, ; Magaziner et al, ; Marottoli et al, ; Morghen et al, ; Oh & Feldt, ; Orive et al, ; Sylliaas et al, ). The following outcome measures were used: the role‐physical of the 36‐Item Short Form Health Survey (SF‐36) (Allegrante et al, ), the physical summary domain of 12‐Item Short Form Health Survey (SF‐12) (Physical Composite Scale scores [PCS‐12]) (Sylliaas et al, ), Lawton‐Brody Instrumental Activities of Daily Living (IADL) Scale (Orive et al, ), Barthel Activities of Daily Living (ADL) Index (Cree et al, ; Kristensen et al, ; Orive et al, ; Sylliaas et al, ), the Nottingham Extended ADL scale (NEADL) (Sylliaas et al, ), adapted functional activity scale ‘Katz index’ (Cobey et al, ) and informal questions on ADL and IADL (Egan et al, ). Mortality: There were six articles that investigated mortality (Hongisto et al, ; Kristensen et al, ; Marottoli et al, ; Mortimore et al, ; Shin et al, ; Thorne et al, ) as measured by death records at various time points post fracture (30 days, 2 months, 6 months, 1 year). Other outcomes: There were six articles investigated other outcomes including: pain, measured by visual analogue scale (VAS) (Orive et al, ), health‐related quality of life as measured by the SF‐36 total score (Gambatesa et al, ), hospital length of stay in days (Kristensen et al, ; Landeiro et al, ) and two articles that investigated the effect on institutionalisation after hip fracture (Hongisto et al, ; Marottoli et al, ). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In western countries 10–20% of the persons are institutionalized when evaluated 6–12 months after the hip fracture [13], and 11% change their dwelling (from home to institution or vice versa) during 4–12 months after the fracture [14]. At one year since the fracture 42% of the patients have not recovered to their pre-fracture mobility level, and 29% do not achieve the same level of activities of daily living that they had before the fracture [15].…”
Section: Introductionmentioning
confidence: 99%